2022
DOI: 10.3390/ijerph19042293
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Adherence and Nutritional Status in Dalmatian Diabetic Hypertensive Patients Regarding Presence of Chronic Kidney Disease—Is There Any Difference?

Abstract: In recent years, the Mediterranean diet has emerged as one of the dietary patterns that could have positive effects on overall health as well in the treatment of non-communicable chronic diseases. The aim of this cross-sectional study was to determine differences in adherence to the Mediterranean diet (MeDi) and nutritional status in patients with type 2 diabetes mellitus (T2DM) and arterial hypertension (AH) regarding the presence of chronic kidney disease (CKD). Two hundred and forty-eight Dalmatian diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Thanks to the presence of high-quality carbohydrates provided by whole grains, nuts, fruits, and vegetables [ 22 ] Med Diet is characterized by a low glycemic index, with positive effects on glucose control, hyperinsulinemia, insulin response and decreased appetite. Furthermore, Med Diet provides 30 to 50 g of fibers per day [ 22 , 48 ] that can contribute to improve postprandial glycaemia and to improve insulin sensitivity. Heindel et al [ 27 ] also in a cohort of 2813 German CKD patients, aged over 60 years, confirmed these evidences.…”
Section: Med Diet and Metabolic Complications In Patients With Ckdmentioning
confidence: 99%
“…Thanks to the presence of high-quality carbohydrates provided by whole grains, nuts, fruits, and vegetables [ 22 ] Med Diet is characterized by a low glycemic index, with positive effects on glucose control, hyperinsulinemia, insulin response and decreased appetite. Furthermore, Med Diet provides 30 to 50 g of fibers per day [ 22 , 48 ] that can contribute to improve postprandial glycaemia and to improve insulin sensitivity. Heindel et al [ 27 ] also in a cohort of 2813 German CKD patients, aged over 60 years, confirmed these evidences.…”
Section: Med Diet and Metabolic Complications In Patients With Ckdmentioning
confidence: 99%